Peningkatan Inovasi Produk Keripik Tempe "Cipta Rasa" di Ketawang Madiun: Enhancement of Tempe Chip’s Product Innovation "Cipta Rasa" in Ketawang Madiun - Ulya, Husna Ni'matul; Shadruddin, Renaldin; Ayu, Diyan Putri (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The small industrial sector is one alternative form to support economic growth in long-term development in Indonesia. Development of an industry must be supported by cooperation between industries in an effort to increase the volume of production. This research was conducted in Ketawang Village, Dolopo Subdistrict, Madiun Regency. Devotional activities are carried out with research-based aimed at increasing the volume of tempeh chips production in Ketawang, Madiun regency. The method used in this devotion is the ABCD method which consists of inculturation, discovery, design, define, and reflection activities. Data is collected through interview methods, observations and documentation. The results of the analysis obtained from the results of the study said that the taste variant on the product has a significant influence on the increase in production volume and economic growth in small industries, which can help the economy in Ketawang because of the main constraints of the lack of income of these chips, namely due to the lack of production volume. Sektor industri kecil merupakan salah satu bentuk alternatif untuk mendukung pertumbuhan ekonomi dalam pembangunan jangka panjang di Indonesia. Perkembangan suatu industri harus didukung dengan kerjasama antar industri dalam upaya meningkatkan volume produksi. Pengabdian dilakukan di Desa Ketawang, Kecamatan Dolopo, Kabupaten Madiun. Kegiatan pengabdian dilakukan dengan berbasis penelitian yang bertujuan untuk meningkatkan volume produksi keripik tempe di Ketawang, Kabupaten Madiun. Metode yang digunakan dalam pengabdian ini adalah metode ABCD yang terdiri dari kegiatan inkulturasi, discovery, design, define, dan reflection. Data dikumpulkan melalui metode wawancara, observasi dan dokumentasi. Berdasarkan hasil penelitian menunjukkan bahwa dengan adanya inovasi varian rasa dan pengemasan pada produk dapat memberikan sumbangan terhadap peningkatan volume produksi dan pertumbuhan ekonomi pada industri kecil, sehingga dapat membantu perekonomian di Ketawang dari kurangnya pendapatan keripik tempe ini, yaitu kurangnya inovasi pada produk.